Resource specific and socially integrated interventions increased profitability of farmers in Varanasi - Roy, Shubhadeep; Singh, S K; Singh, Neeraj; Bhardwaj, D R; Dubey, S K; Behera, T K (Indian Farming, 2022)
Farmer FIRST programme has become a ray of hope for the farmers in the adopted villages. The unique concept of the project has directly benefitted the farmers which they did not experience earlier from any other extension agency. The farmers learnt to believe that they have strengths in their available resources and their  working knowledge is equally important like many others. Now time has come to spread the benefit of the project to the nearby villages through Carpet extension or Horizontal extension approach. Intervention is required towards value-addition of the raw materials like post-harvest processing of the vegetables and egg products which has tremendous market value. Branding and lucrative packaging of the products under Farmer FIRST is next target for capturing best market value. Advanced trainings are required for achieving such objectives and support is needed from government andpolicy makers.